Effects of Forests on Amounts of CO2: Case Study of Kastamonu and Ilgaz Mountain National Parks - Şevik, Hakan; Cetin, Mehmet; Belkayalı, Nur (HARD Publishing Company, 2015)
The CO2 cycle on earth in the last 400,000 years shows that CO2 in the atmosphere increased every 80,000 years and 100,000 years on average and then dropped back later. Although there is 0-0.03% (0-300 ppm) carbon dioxide (CO2) in the air, it has a vital importance because of its amount and variety. Plants reduce the amount of CO2 in the atmosphere with photosynthesis. But plants cannot do photosynthesis in winter or night. As a result, they might have a negative impact on the amount of CO2. In this study, the amounts of air carbon dioxide are measured in forests and urban areas and evaluated depending on season and day or night. Results of our study show that, despite the amount of carbon dioxide decreases in the summer depending on the sunlight, it can double its level at night. In addition to day and night, there is a big difference between the amount of carbon dioxide in terms of summer and winter seasons.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land; 7. Clean energy